2011
DOI: 10.1007/s00134-011-2267-4
|View full text |Cite
|
Sign up to set email alerts
|

The role of renal hypoperfusion in development of renal microcirculatory dysfunction in endotoxemic rats

Abstract: PurposeTo study the role of renal hypoperfusion in development of renal microcirculatory dysfunction in endotoxemic rats.MethodsRats were randomized into four groups: a sham group (n = 6), a lipopolysaccharide (LPS) group (n = 6), a group in which LPS administration was followed by immediate fluid resuscitation which prevented the drop of renal blood flow (EARLY group) (n = 6), and a group in which LPS administration was followed by delayed (i.e., a 2-h delay) fluid resuscitation (LATE group) (n = 6). Renal bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
109
0
6

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 124 publications
(120 citation statements)
references
References 38 publications
5
109
0
6
Order By: Relevance
“…Persistent perfusion deficits and diminished tissue oxygenation have been shown to be of greater magnitude in the highly vulnerable outer medulla compared with the cortex in a variety of experimental models, including total ischemia, radiocontrast nephropathy, and nonsteroidal anti-inflammatory drugand other drug-induced AKI etiologies, including fluid therapy. 23,39 The renal cortex microcirculation is significantly compromised in sepsis models 3,40 and humans, 41 where inhomogeneous patchy areas of microischemia can occur (Figure 2). These heterogeneous areas of hypoxia and normal oxygenation define the nature of hemodynamic alterations leading to inflammation, because it is expected that there is increased reactive oxygen species production associated with hypoxia-normoxia interactions.…”
Section: Peritubular Microcirculation In Akimentioning
confidence: 99%
See 1 more Smart Citation
“…Persistent perfusion deficits and diminished tissue oxygenation have been shown to be of greater magnitude in the highly vulnerable outer medulla compared with the cortex in a variety of experimental models, including total ischemia, radiocontrast nephropathy, and nonsteroidal anti-inflammatory drugand other drug-induced AKI etiologies, including fluid therapy. 23,39 The renal cortex microcirculation is significantly compromised in sepsis models 3,40 and humans, 41 where inhomogeneous patchy areas of microischemia can occur (Figure 2). These heterogeneous areas of hypoxia and normal oxygenation define the nature of hemodynamic alterations leading to inflammation, because it is expected that there is increased reactive oxygen species production associated with hypoxia-normoxia interactions.…”
Section: Peritubular Microcirculation In Akimentioning
confidence: 99%
“…For example, the exact mechanisms by which different fluid compositions (such as normal saline and colloid or buffered solutions) affect renal microcirculation are not well understood, and emerging experimental and clinical data suggest that use of inappropriate fluids or fluid replacement strategies may exert deleterious effects on the microcirculation and renal outcomes. 40,59 Strategies allowing real-time evaluation of microcirculatory fluid and vasopressors responsiveness might be expected to optimize resuscitation effectiveness while limiting the potential to cause harm.…”
Section: Targets To Protect the Nephrovascular Unitsmentioning
confidence: 99%
“…The biologic mechanisms underlying septic AKI have been found to include irregular peritubular capillary flow, 29,30 disturbances in oxygen supply, 9 and mitochondrial dysfunction. 31,32 Less is known, however, about the mechanisms underlying oliguria, despite it being a diagnostic criterion of AKI in several guidelines (e.g., AKIN, RIFLE, and KDIGO).…”
Section: Discussionmentioning
confidence: 99%
“…1,2 The incidence of AKI has steadily increased over the last decade, 3 and its mortality rate has remained high. 4,5 Although basic research has identified several pathways involved in the mechanism of AKI, including inflammation 6,7 and alterations in microcirculation, 8,9 thus enabling the development of new therapeutic strategies, specific treatments that can improve AKI outcome are not yet clinically available. [10][11][12] Notably, only modest histologic changes in the kidney gave been observed in patients with sepsis and in animal models of sepsis, 13,14 whereas septic AKI has a high mortality rate.…”
mentioning
confidence: 99%
“…Clásicamente, la reducción en el flujo sanguíneo renal (FSR) se ha propuesto como el mecanismo más importante en la patogenia de la IRA 5 , sin embargo, la escasa presencia de necrosis reportada en tejido renal de pacientes que fallecen en sepsis con IRA hacen que la pérdida de flujo renal sea un proceso probablemente poco relevante 7,8 . Trabajos clínicos y experimentales recientes enfatizan la importancia de otros mecanismos en la génesis de la IRA en la sepsis, entre estos destaca la intensidad del cuadro inflamatorio y las alteraciones en la determinantes precoces de injuria renal en la sepsis abdominal -t. regueira et al rev Med chile 2014; 142: 551-558 microcirculación más que los cambios globales en el FSR [9][10][11] . El objetivo de este trabajo es evaluar el impacto de los cambios macro-hemodinámicos y del flujo sanguíneo y plasmático renal sobre la función e histología renal en un modelo experimental de sepsis intra-abdominal.…”
unclassified